Physical fitness of Ghanaian physiotherapists and its correlation with age and exercise engagement: a pilot study. Issue 1 (December 2016) - Bonney, Emmanuel
Abstract Background The physical job demands of physiotherapists require optimal level of physical fitness (PF), which is often not evaluated in practice. In this study, we assessed selected components of physical fitness of Ghanaian physiotherapists in relation to their sex, age and frequency of exercise participation. Methods Physiotherapists practicing in four major hospitals within the Accra Metropolis of Ghana were enrolled into this cross-sectional survey. Three major components of physical fitness (flexibility, cardiorespiratory endurance and body composition) were assessed with sit and reach test, 3-min step test and BMI respectively. Unpaired sample t-test was used to determine differences in means of the three components of physical fitness betwwen males and females. Pearson correlation coefficient showed that frequency of exercise engagement and age of the participants correlated with the three components of physical fitness atp  < 0.05. Results The study sample consisted of 40 participants, out of which 23 (58 %) were females. The mean age was (31.5 ± 1.4) years and majority 21 (52.5 %) was within the age range of 20-29 years. Respective mean scores for cardiorespiratory endurance, flexibility and BMI were (98.2 ± 12.9 beat/min), (4.03 ± 6.15 cm) and (23.3 ± 3.4 kg/m2 ). Female participants were significantly more flexible than their male counterparts (5.7 ± 5.3; 1.6 ± 6.6, p = 0.034). There was a positive and significant correlation between the age of the participants and BMI (r = 0.614 and p = 0.017). However, cardiorespiratory endurance was not significantly correlated with age and frequency of exercise engagement. Conclusions The sampled physiotherapists had relatively low physical fitness compared to the age adjusted values. Age and sex are therefore crucial determinants whilst designing programmes aimed at promoting physical fitness in this group.